CCTV: an open door into enterprise and national infrastructure. Issue 2 (February 2018) - Wickes, James
Abstract : CCTV cameras are ubiquitous in today's UK and are trusted to protect people, premises and vital national infrastructure. However, it is becoming increasingly clear that the systems we trust to improve security may not themselves be secure. Some risks can be prevented by understanding the nature of the threat and taking appropriate security precautions, while others are in-built by manufacturers. CCTV cameras are ubiquitous today and are trusted to protect people, premises and vital national infrastructure. However, it is becoming increasingly clear that the systems we trust to improve security may not themselves be secure. As cameras are often outside the scope of an organisation's IT department, it is all too easy for even basic security precautions to be overlooked. However, some insecurities are built-in and organisations may need to review their CCTV strategies, explains James Wickes of Cloudview.